Cultural aspect of translation and communication - Semeniuk, Antonina A.; Семенюк, Антоніна Афанасіївна (Сумський державний університет, 2017)
This article illustrates the connection between culture and communication and then emphasizes the role of culture in translation. This paper has tried to review briefly the scholars' viewpoints and approaches in the field of translation studies to defining the concept of culture. To encourage further exploration and understanding of translation issues the reasons of difficulties arousing in the process of mediating between cultures have been analyzed. Nowadays nobody would argue that each nation possesses a great number of universal features both common and nationally biased ones which are peculiar to a definite genealogically related group of people. The distinguishing characteristics arise from common historical development and the process of evolution which are reflected in material and spiritual life, moral norms, cultural values, canons and people's behaviour and are the background for culture specific elements developing. У статті розглянуто взаємозв'язок між культурою і комунікацією та визначено роль культурного аспекту при перекладі. Коротко проаналізовано точки зору та підходи дослідників до трактування поняття культури. Для заохочення подальших досліджень і розуміння проблем, пов'язаних із перекладом, зроблено спробу дослідити причини виникнення перекладацьких труднощів у процесі взаємодії двох культур.
Культурний аспект комунікації та перекладу
Keywords: culture; communication; translation; translation strategies; a specific language group; культура; комунікація; переклад; стратегія перекладу; особлива мовна група